The Mood guide to fabric and fashion : the essential guide from the world's most famous fabric store - Hartman, Eviana (STC Craft, 2015)
"More than 10 years ago, Tim Gunn and Project Runway introduced millions of viewers to New York's ultimate fabric mecca, Mood Fabrics. Now, the experts behind this fabric power- house bring their fabric and fashion know-how--plus their behind-the-scenes stories--to the sewing public. The Mood Guide to Fabric and Fashion is the ultimate guide for home-sewers, fashion students, aspiring designers, and Project Runway fans who want to learn everything they need to know to choose and use quality fabric. Drawing upon the expertise of the Mood staff, the book teaches readers the fundamentals--from where fabric is produced to the ins and outs of its construction--and features a fabric-by-fabric guide to cottons and other plant fibers, wools, silks, knits, and other specialty fabrics." -- Publisher's description.